Analisis Penerapan Sistem Informasi Akuntansi Berbasis Digitalisasi Dalam Meningkatkan Efisiensi Operasional Perusahaan - Febriyanti, Febriyanti; Masyhuri, Masyhuri (Journal of Economic and Business Advancement, 2026)
This study examines the implementation of digital-based accounting information systems in enhancing operational efficiency within organizations through a conceptual-critical approach grounded in a systematic literature review. The analysis integrates findings from recent academic studies to explore how digital transformation reshapes accounting processes, organizational readiness, and efficiency outcomes. The results indicate that the effectiveness of digital accounting systems is not solely determined by technological adoption but is significantly influenced by mediating mechanisms such as process transformation, information quality, and processing speed. The study identifies key determinants, including digital literacy, organizational capability, and managerial support, as critical enablers of successful implementation, while also highlighting structural constraints such as system complexity and resistance to change.